2002
DOI: 10.1159/000064071
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast Slows the Progression of Advanced Diabetic Nephropathy

Abstract: Background: Tranilast, N-(3,4-dimethoxycinnamoyl) anthranilic acid, suppresses collagen synthesis by various cells, including macrophages and fibroblasts, by interfering with the actions of transforming growth factor-beta 1. We investigated the effect of tranilast on progression of diabetic nephropathy (DN), since this process is associated with accumulation of collagens in the glomerulus and interstitium. Methods: Tranilast (100 mg, 3 times daily) was administered to 9 outpatients with advanced DN who were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Recently, a small pilot study in diabetic patients with advanced diabetic nephropathy demonstrated that tranilast significantly reduced the rate of decline of glomerular filtration rate with a trend toward reduction in proteinuria (Soma et al, 2002). Our findings suggest that tranilast has beneficial effects on early events in the development of diabetic nephropathy even with hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, a small pilot study in diabetic patients with advanced diabetic nephropathy demonstrated that tranilast significantly reduced the rate of decline of glomerular filtration rate with a trend toward reduction in proteinuria (Soma et al, 2002). Our findings suggest that tranilast has beneficial effects on early events in the development of diabetic nephropathy even with hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…Whether this is due to inhibition of Alk5 activity or due to suppression of TGF-␤1-stimulated p38 MAP kinase remains to be determined. Tranilast, a pharmaceutical compound that has been used in animal models of fibrotic disease (40) and in human subjects to treat keloids and to prevent vascular restenosis (33), abrogated both TGF-␤1-stimulated nodule formation and monolayer ECM accumulation (Fig. 7, B and C), at doses similar to those reported to have antiproliferative effects in leiomyoma cells (39).…”
Section: Resultsmentioning
confidence: 77%
“…In the context of the recent pilot study in humans, this study suggests that tranilast may provide a novel strategy for the treatment of progressive kidney disease characterized by fibrotic scarring (28).…”
Section: Discussionmentioning
confidence: 87%
“…In two other studies, the effects of tranilast in diabetic nephropathy were examined. In the first, a pilot study of nine humans with advanced diabetic nephropathy, tranilast was reported to slow the decline in GFR over a 12-mo period, with a nonsignificant trend toward reduction in proteinuria (28). More recently, tranilast was also shown to reduce renal fibrosis and proteinuria in an experimental model of advanced diabetic nephropathy when used as a late intervention (9).…”
Section: Discussionmentioning
confidence: 99%